2006
DOI: 10.1152/ajpregu.00787.2005
|View full text |Cite
|
Sign up to set email alerts
|

The link between cardiac autonomic activity and sleep delta power is altered in men with sleep apnea-hypopnea syndrome

Abstract: We hypothesize that sleep apnea-hypopnea alters interaction between cardiac vagal modulation and sleep delta EEG. Sleep apnea-hypopnea syndrome (SAHS) is related to cardiovascular complications in men. SAHS patients show higher sympathetic activity than normal subjects. In healthy men, non-rapid eye movement (NREM) sleep is associated with cardiac vagal influence, whereas rapid eye movement (REM) sleep is linked to cardiac sympathetic activity. Interaction between cardiac autonomic modulation and delta sleep E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 33 publications
(48 reference statements)
6
37
0
Order By: Relevance
“…For example, aging is associated with a reduction in delta activity and an increase in the LF/HF ratio during NREM sleep [8,30]. Similarly, a number of disorders have been identified that are characterized by low levels of delta activity and high sympathovagal balance, including insomnia [28], fibromyalgia [41], sleep apnea [29], and alcohol dependence [26]. Further, acute stress imposed before sleep has been shown to reduce the amount of delta activity and increase sympathovagal balance during sleep [21].…”
Section: The Effect Of Cardiovascular Activity On Sleepmentioning
confidence: 99%
“…For example, aging is associated with a reduction in delta activity and an increase in the LF/HF ratio during NREM sleep [8,30]. Similarly, a number of disorders have been identified that are characterized by low levels of delta activity and high sympathovagal balance, including insomnia [28], fibromyalgia [41], sleep apnea [29], and alcohol dependence [26]. Further, acute stress imposed before sleep has been shown to reduce the amount of delta activity and increase sympathovagal balance during sleep [21].…”
Section: The Effect Of Cardiovascular Activity On Sleepmentioning
confidence: 99%
“…Modifications in the heart activity was characterized by the RR intervals in normal patients, and reading of visual inspection revealed that the fluctuations of high frequency of the CS (HF reflect cardiac parasympathetic activity) are related with δ frequency band of the brain signals. In 2006, this analysis was extended to male patients diagnosed with sleep apnea, reveling that the respiratory disorders in the sleep, affect the fluctuations of the heart activity [11]. This affectation is reflected by anomalies in the relation between the sympathetic cardiac modulation, the vagal modulation and the δ band subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…These episodes of obstruction are associated with recurrent oxyhemoglobin desaturation and arousals from sleep. Recently, effects of OSA on the interaction between cardiac autonomic control and EEG have been studied [1][2]. Jurysta et al [2] reported that in patients with severe obstructive sleep apnea syndrome (OSAS), coherence between the autonomic cardiac fluctuations and delta sleep EEG was decreased due to a loss of heart rate variability (HRV) during shifts in sleep stages (non REM and REM).…”
Section: Introductionmentioning
confidence: 99%